Journalism's backstage players: the development of journalism professional associations and their roles in a troubled field. Issue 1 (2nd January 2022) - Sherrill, Lindsey; Zhang, Jiehua; Deavours, Danielle; Towery, Nathan; Lyu, Yuanwei; Singleton, William; Kuang, Keqing; Lowrey, Wilson
ABSTRACT: Professional associations' roles in shaping the journalism field have been understudied in news industry research. Adopting a social population ecology perspective, this study provides an across-time analysis of the emergence, rise and variation of the population of US journalism professional associations. In addition to the population demography, content analysis of current association websites was conducted to reveal associations' patterns of development and adoption of roles. Findings suggest associations are turning inward, embracing roles that are internally oriented towards members, their financial struggles, and their identities, while there is less emphasis on externally oriented roles that serve field-wide needs.